A diselenium-bridged covalent organic framework with pH/GSH/photo-triple-responsiveness for highly controlled drug release toward joint chemo/photothermal/chemodynamic cancer therapy. Issue 39 (6th July 2022) - Lou, Han; Chu, Lichao; Zhou, Wenbin; Dou, Jinli; Teng, Xiaotong; Tan, Wei; Zhou, Baolong
Abstract : A novel joint chemo/photothermal/chemodynamic therapy was developed using a pH/GSH/photo triple-responsive 2D-covalent organic framework (Di-Se-Por) as a drug carrier for the passive target treatment of tumors with extraordinarily high efficiency. Abstract : Here, a novel joint chemo/photothermal/chemodynamic therapy was developed using a pH/GSH/photo triple-responsive 2D-covalent organic framework (COF) drug carriers for passive target treatment of tumors with extraordinarily high efficiency. The well-designed COF (DiSe-Por) with simultaneous dynamic diselenium and imine bonds, synthesized by the copolymerization of 4, 4′-diselanediyldibenzaldehyde (DiSe) with 5, 10, 15, 20-(tetra-4-aminophenyl)-porphyrin (Por) via Schiff base chemistry, which was applied as the host for effective encapsulation and highly controlled release of anticancer drug (DOX), was stable under normal physiological settings and can effectively accumulate in tumor sites. After being internalized into the tumor cells, the unique microenvironment i.e., acidic pH and overexpressed GSH, triggered substantial degradation of DiSe-Por-DOX, promoting DOX release to kill the cancer cells. Meanwhile, the breaking of Se–Se bonds boosted the generation of intracellular ROS, disturbing the redox balance of tumor cells. The highly extended 2D structure endowed the drug delivery system with significant photothermal performance. The rise of temperature with external laser irradiation (808 nm) further promoted drug release. Additionally, the phototherapy effect was further augmented after the loading of DOX, guaranteeing an almost complete drug release to tumor tissue. As a result, the triple-responsive drug delivery system achieved a synergistic amplified therapeutic efficacy with a growth inhibitory rate of approximately 93.5% for the tumor xenografted in nude mice. Moreover, the body metabolizable and clearable DiSe-Por-DOX presented negligible toxicities toward major organs in vivo . All these characteristics verified the great potential of DiSe-Por-DOX nanosheets for multi-modality tumor treatment, accelerating the application range of COFs in biomedical fields.